2011
DOI: 10.1111/j.1365-2141.2010.08561.x
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of blood group antigens: hope and reality

Abstract: SummaryIn transfusion medicine, three major issues, i.e. heterogeneity of human blood groups, dependence of blood supply on donation, and shortage of some phenotypes, oblige clinicians to juggle with available biological material to avoid or limit post-transfusion reactions. This 'fact of life' has given impetus to a 30-year-old quest to achieve interchangeability of blood products between donors and recipients by eliminating blood group antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
0
16
0
1
Order By: Relevance
“…Global masking of antigens by incubation of cells with polyethylene glycol has been the focus of numerous in vitro studies but its potential for clinical development has never been demonstrated. The most likely explanations for this situation are unreliable efficacy of PEG treatment and unexpected immune reactions against PEG treated cells [57]. The use of gene transfer techniques to inhibit antigen expression, based on the development of new technological approaches, suggest that, although it is still too soon to judge its usefulness, genetic manipulation of blood group antigens in order to eliminate expression of a blood group system paved a new way of the in vitro production of RBCs showing a selected phenotype.…”
Section: Silencing Of Incompatibility: a New Old Questmentioning
confidence: 99%
See 1 more Smart Citation
“…Global masking of antigens by incubation of cells with polyethylene glycol has been the focus of numerous in vitro studies but its potential for clinical development has never been demonstrated. The most likely explanations for this situation are unreliable efficacy of PEG treatment and unexpected immune reactions against PEG treated cells [57]. The use of gene transfer techniques to inhibit antigen expression, based on the development of new technological approaches, suggest that, although it is still too soon to judge its usefulness, genetic manipulation of blood group antigens in order to eliminate expression of a blood group system paved a new way of the in vitro production of RBCs showing a selected phenotype.…”
Section: Silencing Of Incompatibility: a New Old Questmentioning
confidence: 99%
“…While overexpression of a blood group antigen has no direct therapeutic value in transfusion medicine, it can be useful in the development of diagnostic tools needed for immuno-hematologic testing of blood products [57][58][59].…”
Section: Towards the Creation Of New Diagnostic Toolsmentioning
confidence: 99%
“…First, the steady increase in blood product consumption and shortage of some phenotypes [87]. Second, a decline in regular blood donations over the next decades in many countries as a result of the aging of populations.…”
Section: Future Perspectivementioning
confidence: 98%
“…In the 1980s, two methods were proposed for phenotype conversion to obtain 'universal' RBCs, i.e. treatment with glycosidases to eliminate AB antigens and antigen camouflage with polyethylene glycol derivatives [28]. In 2009, focusing on the Kidd Blood group system, experiments with lentiviral vectors demonstrated the possibility of a third technique, i.e.…”
Section: Towards Proof Of Principle and Applicationmentioning
confidence: 99%